1994
DOI: 10.1002/ijc.2910560124
|View full text |Cite
|
Sign up to set email alerts
|

Unusually marked hypoxic sensitization to indoloquinone E09 and mitomycin C in a human colon‐tumour cell line that lacks DT‐diaphorase activity

Abstract: Studies with purified DT-diaphorase have shown that the enzyme is capable of catalyzing a two-electron reduction of the novel indoloquinone E 0 9 to a DNA-damaging alkylating species. The aim of this study was to determine to what extent DT-diaphorase may be involved in the metabolic activation of E09 and mitomycin C in both aerobic and hypoxic conditions. Two human colon-carcinoma cell lines were used; H l 2 9 has high levels of DT-diaphorase whilst BE lacks this activity because of a point mutation in the NQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…1B), there was a ∼10-fold difference in aerobic sensitivity between the most sensitive (RIF-1) and resistant (HT29 and SKOV3) cell lines. The similar pattern for the nitro and amino compounds suggests that the differences in aerobic sensitivity to the nitro prodrugs are not a result of their aerobic activation in a subset of cell lines, unlike the situation with quinone or dinitrobenzamide HAPs, which are activated by variably expressed two-electron reductases (10,12). Consistent with this, the lower hypoxic selectivity of the nitro prodrugs in HT29 relative to UV4 and RIF-1 reflects resistance under hypoxia rather than sensitivity under aerobic conditions [as would occur if, for example, the high activity of DT-diaphorase in HT29 cells (10) resulted in two-electron activation].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1B), there was a ∼10-fold difference in aerobic sensitivity between the most sensitive (RIF-1) and resistant (HT29 and SKOV3) cell lines. The similar pattern for the nitro and amino compounds suggests that the differences in aerobic sensitivity to the nitro prodrugs are not a result of their aerobic activation in a subset of cell lines, unlike the situation with quinone or dinitrobenzamide HAPs, which are activated by variably expressed two-electron reductases (10,12). Consistent with this, the lower hypoxic selectivity of the nitro prodrugs in HT29 relative to UV4 and RIF-1 reflects resistance under hypoxia rather than sensitivity under aerobic conditions [as would occur if, for example, the high activity of DT-diaphorase in HT29 cells (10) resulted in two-electron activation].…”
Section: Discussionmentioning
confidence: 87%
“…These hypoxia-activated prodrugs (HAP) act as direct oxygen sensors through the ability of O 2 to inhibit the first step in their reductive metabolism, usually by reoxidizing the initial radical intermediate (9). Several HAPs are currently in clinical trial (N-oxides tirapazamine and banoxantrone, nitro compounds PR-104 and TH-302, and quinones apaziquone and RH1), and the approved drug mitomycin C has weak selectivity for hypoxic cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…A possibility supported by the fact that cell lines with very low NQO1 but overexpressing P450 reductase do not show enhanced sensitivity to RH1 (49). NQO1 has been reported to be up-regulated under hypoxic conditions (33,34). Consequently, under hypoxia, RH1 is likely to be more stable following any one-electron reduction.…”
Section: Pharmacodynamic Properties Of Rh1mentioning
confidence: 99%
“…Whereas numerous in vitro-based studies have shown that NQO1 plays a key role in the mechanism of action of a number bioreductive drugs, such as clinically active mitomycin C (MMC; 14, 24 -28), it is clear that there exits a far from simple relationship between in vivo drug activity and clinical efficacy and NQO1 expression (29 -32) both under hypoxic and aerobic conditions (33,34).…”
mentioning
confidence: 99%
“…The cellular studies using dicumarol as NQO1 enzyme inhibitor indicated that bioactivation by the obligatory two-electron reducing enzyme NQO1 might be especially important for the cytotoxicity of mitomycin C (2,7,8). On the other hand, the cells expressing higher levels of NQO1 failed to show increased sensitivity to mitomycin C compared with cells of similar origin containing normal levels of NQO1 (9,10). The cellular studies have shown a role of NQO2 in metabolic activation of mitomycin C and other drugs leading to cytotoxicity and cell death (11,12).…”
Section: Introductionmentioning
confidence: 99%